Evidence of seed dispersal of Virola surinamensis (Myristicaceae) by a catfish in Eastern Amazonia, Brazil - Freitas, Tiago Magalhães da Silva; Almeida, Vitor Hudson da Consolação; Montag, Luciano Fogaça de Assis (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
The aim of this study was to investigate the potential of the midnight catfish Auchenipterichthys longimanus (Siluriformes: Auchenipteridae) to disperse seeds of Virola surinamensis in the Caxiuanã National Forest, in the Eastern Amazon, Brazil. We conducted an experiment to compare germination rates and times of seeds from stomachs of fish with those collected from nutmeg trees (treatment I), with seeds with intact aril (treatment II), and with seeds without aril (treatment III). Treatment III exhibited the highest percentage of germination (90%), followed by treatments I (69%) and II (57%). Time of germination also varied among groups. Seeds with intact aril showed longer average germination times (≈ 33 days to germinate) when comparing with seeds from the stomach of the fish (≈ 28 days) and seeds without aril (≈ 25 days). Our results showed that the frugivorous catfish did not damage the nutmeg seeds and support the conclusion that A. longimanus may be an effective disperser of V. surinamensis in riparian forests of the Caxiuanã region. These findings are consistent with other studies that have shown that many plant species to be dispersed by fishes